Modelling surface‐water depression storage in a Prairie Pothole Region. Issue 4 (8th February 2018) - Hay, Lauren; Norton, Parker; Viger, Roland; Markstrom, Steven; Steven Regan, R.; Vanderhoof, Melanie
Abstract: In this study, the Precipitation‐Runoff Modelling System (PRMS) was used to simulate changes in surface‐water depression storage in the 1, 126‐km 2 Upper Pipestem Creek basin located within the Prairie Pothole Region of North Dakota, USA. The Prairie Pothole Region is characterized by millions of small water bodies (or surface‐water depressions) that provide numerous ecosystem services and are considered an important contribution to the hydrologic cycle. The Upper Pipestem PRMS model was extracted from the U.S. Geological Survey's (USGS) National Hydrologic Model (NHM), developed to support consistent hydrologic modelling across the conterminous United States. The Geospatial Fabric database, created for the USGS NHM, contains hydrologic model parameter values derived from datasets that characterize the physical features of the entire conterminous United States for 109, 951 hydrologic response units. Each hydrologic response unit in the Geospatial Fabric was parameterized using aggregated surface‐water depression area derived from the National Hydrography Dataset Plus, an integrated suite of application‐ready geospatial datasets. This paper presents a calibration strategy for the Upper Pipestem PRMS model that uses normalized lake elevation measurements to calibrate the parameters influencing simulated fractional surface‐water depression storage. Results indicate that inclusion of measurements that give an indication of the change in surface‐water depression storage in the calibration procedure resulted in accurate changes in surface‐water depression storage in the water balance. Regionalized parameterization of the USGS NHM will require a proxy for change in surface‐storage to accurately parameterize surface‐water depression storage within the USGS NHM.